Imaging features of pancreatic extragastrointestinal stromal tumors: a case report and literature review - Xu, Jian-Xia; Gu, Meng-Yin; Wang, Yi-Hua; Huang, Xiao-Shan; Duan, Jia-Qi; Zheng, Xiao-Zhong; Chen, Xi-Xi; Yu, Ri-Sheng; Xiang, Jun-Yi (Frontiers in Oncology, 2025)
Pancreatic extra-gastrointestinal stromal tumors (pEGISTs) are exceedingly rare, accounting for less than 5% of all extra-gastrointestinal stromal tumors (EGISTs). We report a case involving a 62-year-old woman who presented with a hypervascular pancreatic mass. Postoperative histopathological examination confirmed the diagnosis of a gastrointestinal stromal tumor (GIST). The neoplastic cells exhibited a spindle-shaped morphology without evident necrosis on histologic sections. Immunohistochemical analysis demonstrated strong, diffuse positivity for CD117, DOG-1, and CD34. Notably, the imaging characteristics of this pEGISTs displayed several distinctive features, including intralesional “island-like” enhancement, peripheral nodular enhancement, and prominent vascular “staghorn” patterns. Although histopathology remains the gold standard for definitive diagnosis of pEGISTs, correlating clinical presentation with these unique radiologic features can substantially improve diagnostic accuracy for radiologists. Additionally, we provide a comprehensive review and discussion of the current literature on the clinical and imaging hallmarks of pEGISTs.